Pengaruh Pengungkapan Technological Capital terhadap Nilai Perusahaan pada Jakarta Islamic Index - Wangsih, Ingkak Chintya; Rosidawaty, Rosidawaty; Gumilang, Andika Mugi; Septiani, Tanti; Pane, Zulfikar Ikhsan (Penerbit Goodwood, 2025)
Purpose: This study aims to determine how disclosing information about a company's technological assets (technological capital) affects its value. This study focuses on companies listed on the Jakarta Islamic Index (JII). Methodology/approach: This study examined 16 companies listed on the JII between 2019 and 2023. A total of 75 annual reports were selected using purposive sampling method. This study used content analysis to measure the extent of technological capital disclosure. Panel data regression analysis was performed using EViews software. Results/findings: The study found that companies that share more information about their technology tend to have higher values. This implies that being open about technological strengths helps build investor trust, which improves market performance. Conclusions: Disclosure of technological capital positively and significantly impacts firm value. Transparency in this area builds investor trust, reduces uncertainty about innovation capacity, and enhances both competitiveness and market performance. Limitations: This study includes only companies from the Jakarta Islamic Index and uses secondary data. It does not consider the reasons why companies disclose certain information. Contribution: This study contributes to research on Islamic capital markets and intellectual capital by highlighting the importance of technological disclosure. It introduces technological capital as a measurable factor in an Islamic index, which has not been widely studied. This can benefit academics, investors, and policymakers interested in Islamic finance and corporate transparency.